Developing Pragmatic Competence in the EFL Context: Opportunities and Challenges. - SEGUENI, Lamri (Sciences humaines; Vol. 35 (2014): SCIENCES HUMAINES)
يعتبر تدريس القدرات التداولية إحدى الجوانب المهملة في برامج تدريس اللغة الإنجليزية في الجزائر.هنالك ندرة حقيقية لتداولية  في المضامين وتقديمها مهمش بالمقارنة بالجوانب الأخرى للغة. ولذلك و من اجل تقوية قدرات التواصل لدى الطلبة بات من الضروري الابتعاد عن الأطر التعليمية السابقة و المبنية    على اكتساب قواعد نظرية إلى نظرة تواصلية شاملة .          هذا المقال يتناول تشخيص العوائق التي تواجه تدريس التداولية في اللغة الإنجليزية كلغة أجنبية. كما يهدف      إلى اقتراح الأطر المناسبة لتنمية هذه القدرة.               Teaching pragmatics is one of the neglected aspects in English language teaching in Algeria. There is a total dearth of pragmatic contents and their presentations are marginalized as compared to other language items. Therefore, in order to make learners communicatively competent, there should be a shift from previous theoretical frameworks which considered language as a formal system based on the acquisition of rules, towards a more communicative orientation. The current paper, therefore, looks into the challenges and opportunities in teaching pragmatics to language learners in the EFL context and the way to forward it. Key words: Pragmatic/Competence/EFL/ Context/Opportunities